Determination of the Behavioral Effect of Ultrasonic Sounds at Different Frequencies and Waveforms on Ephestia kuehniella Zeller (Lepidoptera: Pyralidae) - Yetkin, Cemil; Emine ÇIKMAN (ISPEC Journal of Agricultural Sciences, 2021)
The biotechnical struggle against pests aims to reduce the damage of insects below the economic damage threshold with the help of all sound, odor and visual factors that negatively affect the insect population. One of the biotechnical control methods is the use of sound waves against insects. Moths including Ephestia kuehniella Zeller (Lepidoptera: Pyralidae), detect the sounds emitted by predator bats at 20-200 kHz with their tympanal organs. During flight, a pyralid moth which detects ultrasonic sound, immediately moves away from the source of sound with a sudden maneuver or remains motionless by throwing itself to the ground. Based on this behavior of pyralid moths, sine and square waveforms between 40-50 kHz (21 different frequences) were applied on E. kuehniella, in a choice test system in laboratory conditions. Ultrasonic waves were applied to E. kuehniella adults from a distance of 50 cm, who were in the choice tunnel. Motionless or escape behavior of the moth when exposed to ultrasonic sounds, was investigated. As a result of the research, it was determined that E.kuehniella, which were released in the choice tunnel, remained motionless both in the non-sound control application and against all applied frequency and waveforms.